Catholic Health Band. - Ramya, K. Ruth; D., Chandrika; K., Nikhitha; T., Niteesha; P., Pravallika (Turkish Journal of Physiotherapy Rehabilitation, 2021)
With the forge ahead of technology being produced, the future looks scintillating for the field of medicine. The internet of things, generally referred to as IoT, has made its existence known unequivocally in the field of the medical sector. The Internet of things is a framework that can move information over a network without expecting human-to-human interactivity. Remaining in accordance with the IoT vision we propose a smart Catholic Health Band which relies on different technologies, specifically RFID, WSN, and smart mobile, cooperating with one another by means of a Constrained Application Protocol/IPv6 over low-power wireless personal area network/representational state transfer network infrastructure. Catholic Health Band is a real-time monitoring wearable device with sensors, which can be carried out by patients. It also perceives drop downs and disruptions which can be immensely useful for the elderly suffers and convalescents. These sensors transmit information about patients' fundamental signs to social insurance suppliers in authentic time. Any changes in temperature, circulatory strain (blood pressure), heartbeat, and pulse are in a split second passed on to specialists or attendants, who would then be able to give prompt ministration. The aim of this paper is to create a brilliant gadget from contrivance utilizing the Internet of Things associated with a cellular message to the caretaker or guardian.